How do new organizational practices shape production jobs ? Results from a matched employer-employee survey in French manufacturing - Greenan, Nathalie; Mairesse, Jacques (Noisy-le-Grand, 2003)
"In this paper, we use a French matched employer-employee survey, the C.O.I. survey, conducted in 1997, to describe the general features of organizational change in manufacturing firms with more than fifteen employees. We work with a sample of 3,286 firms and two samples of “core” employees (with at least a year of seniority): 2,612 blue collars and 1,162 technicians and supervisors. We have two main aims: discuss new ways of measuring organizational change, allowing for diversity in its orientation and analyze empirically how new organizational practices have been shaping production jobs in French manufacturing firms throughout the nineties. In the first section, we describe the statistical anatomy of organizational change, using the point of view given by management in the business section of the C.O.I survey. We then turn to the labor force section of the survey where we analyze the patterns of work organization in our samples of blue collars and of technicians and supervisors. We finally confront the information gathered on these two different levels. We find that a common ingredient to new organizational practices is the production of a collective knowledge on the shop floor allowing continuous improvement of the production process. In other words, organizational changes would drive a new way of rationalizing knowledge making where production workers are asked to explicitly contribute to technological progress. The structure of blue-collar effort becomes more complex as they are required to participate intensively both in information and production flows. However, some results suggest that the core of organizational changes in the nineties has changed direction after the 1993 recession, switching from product and quality strategies to low cost strategies and implying more pressure on the work of technicians and supervisors and a slowdown in the “enrichment” of blue-collar jobs." (Authors' abstract)